Systemic Infection by Pseudomonas aeruginosa in a Dog - da Silva, Layze Cilmara Alves; do Nascimento Pessoa, Danielle Aluska; Maia, Lisanka Ângelo; Matos, Rodrigo Antonio Torres; Macêdo, Meire Maia da Silva (Acta Scientiae Veterinariae, 2016)
Background: Pseudomonas aeruginosa is an important pathogen frequently associated with nosocomial infections affecting mainly immunosuppressed patients. In Veterinary Medicine, infections caused by P. aeruginosa are becoming increasingly frequent; infections are related to intrinsic or acquired resistance mechanisms, which limit the choice of effective agents. Case: This study describes the case of a four-month-old male Pitt Bull dog treated at the Small Animal Internal Medicine service of the Veterinary Hospital at the Health and Rural Technology Center of Federal University of Campina Grande, Patos/Paraíba. The patient presented with apathy, inappetence, moderate dehydration, tachypnea, tachycardia, hyperthermia, pale mucosae, small lesions in the pelvic limbs, with edema and subsequent widespread petechiae. Treatment with intravenous fluid therapy using 0.9% NaCl with B-complex vitamins, and 20 mg/kg cephalexin every 12 h was established. The patient did not respond well to treatment, and died two days later. Necropsy was performed at the Veterinary Pathology sector of the Hospital and histopathological findings revealed focally extensive areas of necrosis associated to myriads of bacteria and mild mononuclear inflammatory infiltrates in the liver, heart and kidneys. Secretions and organ fragments were submitted to the Microbiology Laboratory of the same institution, which identified a systemic bacterial infection caused by P. aeruginosa. In vitro bacterial susceptibility to 15 different antimicrobials was assessed using the Bauer-Kirby disk diffusion test in Mueller Hinton agar. The agent exhibited multiple resistance to enrofloxacin, cephalexin, ceftiofur, gentamicin, imipenem, kanamycin, cephalothin, norfloxacin, amoxicillin, polymyxin B, ampicillin, tetracycline, and penicillin. It was sensitive to amikacin and neomycin only. Phenotypic detection was performed via disk approximation test (D-test) established by the Clinical and Laboratory Standard Institute (CLSI), which showed metallo-beta-lactamase (MBLs)-producing bacteria. Discussion: Clinical-pathological and microbiological aspects confirmed a systemic infection by P. aeruginosa characterized by yellowish nodular lesions and occasional hemorrhage, associated with myriads of bacteria in the lumen of the vessels in multiple organs. The agent was probably disseminated hematogenously, and it is likely that the cutaneous lesions in the pelvic limbs were the entry point. Treatment using cephalexin proved to be inefficient for the animal of the present study, which may have been be due to the patient’s immunosuppression and the agent’s natural or acquired resistance to this drug; therefore, special care needs to be taken when using these antibiotics as a preventive measure against the dissemination of gram-negative (MBL)-producing P. aeruginosa. We can conclude that P. aeruginosa may cause systemic infection in dogs. Amikacin and neomycin are the most efficient antimicrobials for the in vitro elimination of the bacteria; however, other studies on the use of these drugs in vivo are needed. Considering the occurrence of resistance to multiple antimicrobials and the production of MBLs observed in this study, it is important to monitor P. aeruginosa through phenotypical and antimicrobial susceptibility tests to verify its level of resistance in diseases in Veterinary Medicine. Keywords: microbiological, internal medicine, infections, Veterinary Medicine.